Game characteristics in professional tennis at different levels of international tournaments - Carboch, J. (International Journal of Applied Exercise Physiology, 2021)
Fast tennis shots and quick movements are required in professional tennis; however, the game performance can be different in various international tournament levels. The aim is to analyse and compare game characteristics and the frequency of rally shots in male matches at the Australian Open and at the ITF Men's World Tennis Tour tournament, the Milovice Open. We analysed 1,738 points in seven matches at the Australian Open and 1629 points in fifteen matches at the Milovice Open. Based on previous research, selected game characteristics such as point duration, rally length, time between the points, rally pace or work to rest ratio were compared between the tournaments. In both tournament levels, 60 % of rallies were finished within the first four shots of the rally. Other observed variables were also very similar in both tournaments, but the rally pace was significantly different. The players played in a significantly faster rally pace at the Australian Open (1.22±0.03) compared to the Milovice Open (1.27±0.05), p=0.02. These findings show a difference in game performance between the top and lower international level of tennis tournaments. Coaches can use information about the match game performance to optimize the practice sessions.